DON in pediatric cerebral malaria, a phase I/IIA dose-escalation safety study: study protocol for a clinical trial - Nginache Nampota-Nkomba; Osward M. Nyirenda; Jane Mallewa; Yamikani Chimalizeni; Nettie Dzabala; Michael P. Fay; Mathangi Gopalakrishnan; Matthew B. Laurens; Nicole F. O’Brien; Louis H. Miller; Susan K. Pierce; Brittany A. Riggle; et al. (Trials, 2024)
Abstract Background Despite treatment with highly effective antimalarial drugs, malaria annually claims the lives of over half a million children under 5-years of age in sub-Saharan Africa. Cerebral malaria (CM), defined as Plasmodium falciparum infection with coma, is the severe malaria syndrome with the highest mortality. Studies in the CM mouse model suggest that a T cell-mediated response underlies CM pathology, opening a new target for therapy in humans. This trial aims to establish the preliminary safety of one such novel therapy, the glutamine antagonist 6-diazo-5-oxo-L-norleucine (DON). Methods In this phase I/IIa dose-escalation clinical trial, a single dose of intravenous (IV) DON is administered to three participants groups—healthy adults and adults with uncomplicated malaria, then pediatric participants with CM—to primarily assess safety. The secondary objective of this trial is to assess pharmacokinetics of DON over a range of doses. The open-label adult portion of the trial enrolls 40 healthy adults concurrently with 40 adults with uncomplicated malaria. Cohorts of 10 participants receive a single IV dose of DON with doses escalating between cohorts from 0.1 mg/kg, 1.0 mg/kg, 5.0 mg/kg, to 10 mg/kg. Following subsequent safety review, a randomized, double-blind, and placebo-controlled pediatric study enrolls 72 participants aged 6 months to 14 years with CM. The pediatric portion of the study minimally spans three malaria seasons including a planned interim analysis after 50% of pediatric enrollments. The first half of pediatric participants receive DON 0.1 mg/kg, 1.0 mg/kg, or placebo. Dosing for the second half of pediatric participants is informed by the safety and preliminary efficacy results of those previously enrolled. The pediatric portion of the study has an exploratory outcome evaluating the preliminary efficacy of DON. Efficacy is assessed by diagnostics predictive of CM outcome: electroencephalography (EEG), magnetic resonance imaging (MRI), and transcranial doppler (TCD), measured before and after DON administration. All participants with malaria receive standard of care antimalarials in accordance with local guidelines, regardless of study drug dose group. Discussion This preliminary safety and efficacy study evaluates DON, a candidate adjunctive therapy for pediatric CM. If results support DON preliminary safety and efficacy, follow-up phase II and III clinical trials will be indicated. Trial registration This trial was registered on ClinicalTrials.gov on 28 July 2022 (NCT05478720).